2003
DOI: 10.1063/1.1602554
|View full text |Cite
|
Sign up to set email alerts
|

A quantum weak energy inequality for spin-one fields in curved space–time

Abstract: Quantum weak energy inequalities (QWEI) provide state-independent lower bounds on averages of the renormalized energy density of a quantum field. We derive QWEIs for the electromagnetic and massive spin-one fields in globally hyperbolic space–times whose Cauchy surfaces are compact and have trivial first homology group. These inequalities provide lower bounds on weighted averages of the renormalized energy density as “measured” along an arbitrary timelike trajectory, and are valid for arbitrary Hadamard states… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
130
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(132 citation statements)
references
References 55 publications
2
130
0
Order By: Relevance
“…In fact, the following theorem holds: Let u, v be distributions on X. If WF(u) + WF(v) (element-wise addition) does not contain a zero cotangent vector in T * X, then the distributional product uv is naturally 30 defined. More generally, for a set of n distributions, if ∑ j WF(u j ) does not contain a zero cotangent vector, then ∏ j u j is defined.…”
Section: Quantum Gravitymentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the following theorem holds: Let u, v be distributions on X. If WF(u) + WF(v) (element-wise addition) does not contain a zero cotangent vector in T * X, then the distributional product uv is naturally 30 defined. More generally, for a set of n distributions, if ∑ j WF(u j ) does not contain a zero cotangent vector, then ∏ j u j is defined.…”
Section: Quantum Gravitymentioning
confidence: 99%
“…This yields a satisfactory theory at the level of the algebra A , see e.g. [30,33,74] for details. But it is far from clear how to construct an analog of B I for models with interaction, such as Yang-Mills theory, by proceeding this manner.…”
Section: Yang-mills Fieldsmentioning
confidence: 99%
“…Various authors have suggested employing such effects to sustain exotic spacetime geometries containing wormholes [31] or 'warp drive' bubbles [2]. Such suggestions are, however, severely constrained [23,33] by the existence of bounds, known as quantum inequalities (QIs) or quantum weak energy inequalities (QWEIs) [13,14,16,18,19,20,21,22,24,34] which impose limitations on the magnitude and duration of negative energy densities. To give an example, let ρ(t) ψ be the energy density of the free scalar field 2 measured along an inertial worldline in Minkowski space.…”
Section: Introductionmentioning
confidence: 99%
“…For any free field in a (globally hyperbolic) spacetime, there exist zero-mean-field reference states, called Hadamard states, characterized by welldefined two-point correlators [16,19,25]. Such a reference state allows us to perform normal ordering via the point-splitting approach.…”
Section: Estimation Of Spacetime Perturbationmentioning
confidence: 99%
“…The aim of algebraic quantum field theory is to put quantum field theory on rigorous mathematical footing, while the aim of what might be termed pragmatic quantum field theory is to make experimental predictions [14,15]. Strides toward connecting the two have been made recently [5,[16][17][18][19], and this progress makes the current work possible.…”
Section: Introductionmentioning
confidence: 99%